A lithium battery negative electrode sheet, a lithium battery comprising the same, and a preparation method thereof
Patent Information
- Application Number
- CN202611468161.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本发明旨在提供一种锂电池负极片,以解决现有技术中锂电池负极涂层通常无法同时满足高能量密度和快充性能的问题
本发明通过硅基与碳基材料粒径搭配,并且通过理论计算公式,获得合理的硅碳与石墨的粒径搭配,即上下层孔隙率不同的配方,在相同压力下形成不同孔隙率的活性层,即在一次辊压下可制备双层孔隙率结构的负极极片,通过双层涂布在负极设置双层结构,靠近集流体的第一负极活性物质层为高压实、低孔隙率层,靠近隔膜的第二负极活性物质层为低压实、高孔隙率层,同时在高压实低孔隙率层加入棒状介孔材料,进一步改善吸液,在负极中构建快速的锂离子扩散通道,保证高能量密度的同时大幅提高快充性能,且方法简单,可实现批量化生产。
Smart Images

Figure CN123017885A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium battery technology, and relates to a lithium battery negative electrode sheet, a lithium battery containing the same, and a method for preparing the same. Background Technology
[0002] With the vigorous promotion of new energy vehicles, the demand for power batteries is increasing daily. The demand for high-energy-density, high-safety, and long-cycle-life lithium-ion power batteries is particularly prominent. At the same time, the charging speed of new energy vehicles is a major obstacle to their rapid popularization. However, high energy density and fast-charging performance of rechargeable batteries are often conflicting. High-energy-density rechargeable batteries typically have poor fast-charging performance. Therefore, improving rate performance while maintaining high energy density is crucial.
[0003] For existing high-energy-density electrodes, those skilled in the art mainly employ the following methods to improve fast-charging performance: (1) Prepare an electrode with a porosity gradient coating by coating a current collector with active material slurry containing different pore-forming agent concentrations to improve the penetration and wetting of electrolyte and enhance the transport of lithium ions / electrons in the electrode. (2) Electrode sheets with different porosity gradients were prepared by multiple layer coating and then roll pressing. (3) Use laser to drill holes along the thickness direction of the electrode to improve the rate performance of the battery. (4) Electrode sheets with different porosity gradients are prepared by double-layer simultaneous coating and subsequent roll pressing.
[0004] However, in the actual research and development and production process, the following problems still exist in the preparation process of the above-mentioned improved method: (1) The uneven local lithium insertion / extraction in the micron-sized pores formed by the pore-forming agent leads to a short cycle life; (2) The multi-layer coating process is complicated and requires rolling after each coating, which increases production costs. In addition, there are obvious interfaces between different layers. For silicon-containing anodes, due to the large volume expansion of silicon itself, the electrode sheet will delaminate during the cycle, resulting in poor structural stability and short cycle life. (3) Laser-induced hole formation has a large heat-affected zone, damaging the active material and binder around the hole, resulting in severe powder shedding and increasing the risk of battery short circuit. Therefore, the existing manufacturing methods for high-energy-density, high-rate electrode sheets still need improvement.
[0005] (4) With simultaneous double-layer coating, how to design the upper and lower layers to ensure that different porosities of the lower layer are achieved in one roll pressing, and there is no theoretical calculation method for how to combine multiple active substances to achieve porosity gradient, which is not conducive to promotion and application. Summary of the Invention
[0006] The present invention aims to provide a lithium battery negative electrode sheet to solve the problem that the existing lithium battery negative electrode coatings usually cannot simultaneously meet the requirements of high energy density and fast charging performance.
[0007] This invention provides a lithium battery negative electrode sheet, comprising a current collector, a first negative electrode active material layer, and a second negative electrode active material layer; The current collector is made of copper foil; The first negative electrode active material layer is disposed between the current collector and the second negative electrode active material layer; The second negative electrode active material layer is disposed on the surface of the first negative electrode active material layer; Let the volume fraction of the particle size of the material in the first and second negative electrode active material layers be . The particle size of any particle size in the particle size distribution curve of the active substance is . The minimum particle size in the particle size distribution curve of the active substance is The maximum particle size in the particle size distribution curve of the active substance is and the particle size distribution modulus of the active material particles is ; The particle size distribution in both the first and second negative electrode active material layers is set to... ; Volume fraction of particle size The value range is set to 0 to 100%; The particle size distribution modulus of the active material particles in the first negative electrode active material layer The range of values is set to ; The particle size distribution modulus of the active material particles in the second negative electrode active material layer The range of values is set to >0.6 or <0.2.
[0008] Furthermore, let the limiting compaction density of the first negative electrode active material layer be... The ultimate compaction density of the second negative electrode active material layer is ,satisfy and .
[0009] Furthermore, the first negative electrode active material layer includes a first active material, a first conductive agent, a first dispersant, a first binder, and a rod-shaped mesoporous liquid-absorbing material; The first active material includes a first carbon-based active substance and a first silicon-based active substance; The rod-shaped mesoporous liquid-absorbing material is configured as a rod-shaped mesoporous tin-based material, and its pore size is configured as 2nm to 100nm.
[0010] Furthermore, the mass percentages of the first active material, the first conductive agent, the first dispersant, the first binder, and the rod-shaped mesoporous liquid-absorbing material are set as follows: 90-99 wt% of the first active material, 0.01-3 wt% of the first conductive agent, 0-3 wt% of the first dispersant, 0.01-5 wt% of the first binder, and 0.01-1 wt% of the rod-shaped mesoporous liquid-absorbing material.
[0011] Furthermore, the second negative electrode active material layer includes a second active material, a second conductive agent, a second dispersant, and a second binder; The second active material includes a second carbon-based active substance and a second silicon-based active substance; The mass percentages of the second active material, the second conductive agent, the second dispersant, and the second binder are set as follows: 90-99 wt% of the second negative electrode active material, 0.01-3 wt% of the second conductive agent, 0-3 wt% of the second dispersant, and 0.01-5 wt% of the second binder.
[0012] Furthermore, let the volume average particle size of the first carbon-based active material be... The volume average particle size of the second carbon-based active material is The volume average particle size of the first silicon-based active material is And the volume average particle size of the second silicon-based active material is ; in: , , The value ranges from 8μm to 23μm. The value ranges from 4μm to 16μm. The value ranges from 6μm to 12μm. The value ranges from 2μm to 5μm.
[0013] Furthermore, the first conductive agent is set as any one or any combination of two or more of the following: conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotube, graphene, metal powder and metal fiber. The second conductive agent is set as any one or any combination of two or more of the following: conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotube, graphene, metal powder and metal fiber.
[0014] Furthermore, the first adhesive is set as any one or any combination of two or more of the following: styrene-butadiene rubber, polyacrylic acid, lithium polyacrylate, carboxymethyl chitosan, sodium alginate, polyvinyl alcohol, polyurethane, polyvinylidene fluoride, and polyvinylidene fluoride-hexafluoropropylene copolymer. The second adhesive is set as any one or any combination of two or more of the following: styrene-butadiene rubber, polyacrylic acid, lithium polyacrylate, carboxymethyl chitosan, sodium alginate, polyvinyl alcohol, polyurethane, polyvinylidene fluoride, and polyvinylidene fluoride-hexafluoropropylene copolymer.
[0015] Furthermore, the first dispersant is configured as lithium carboxymethyl cellulose and / or sodium carboxymethyl cellulose; The second dispersant is configured as lithium carboxymethyl cellulose and / or sodium carboxymethyl cellulose.
[0016] Furthermore, the first carbon-based active material is set as any one or any combination of two or more of natural graphite, artificial graphite or hard carbon. The second carbon-based active material is set as any one or any combination of two or more of natural graphite, artificial graphite or hard carbon.
[0017] Furthermore, the first silicon-based active material has a mass percentage of 3-50 wt% in the first negative electrode active material layer, the second silicon-based active material has a mass percentage of 1-40 wt% in the second negative electrode active material layer, and the mass percentage of the first silicon-based active material in the first negative electrode active material layer is greater than or equal to the mass percentage of the second silicon-based active material in the second negative electrode active material layer. The mass ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:9 to 9:1.
[0018] As a further aspect of the present invention, the present invention also provides a lithium battery, including a positive electrode, an electrolyte, a separator, and a lithium battery negative electrode as described above.
[0019] As a further aspect of the present invention, a method for preparing a lithium battery is also provided, comprising the following steps: Step ①: Preparation of the first negative electrode active material layer; The first conductive agent powder, the first binder powder, and the rod-shaped mesoporous liquid-absorbing material are mixed and stirred, and then moistened with solvent; The mixture is diluted with solvent, stirred, dispersed, kneaded and scraped, and then premixed first carbon-based active material and first silicon-based active material are added to form a mixture to make the mixture wet; After dilution with solvent, stirring, dispersing, kneading and scraping are performed, followed by vacuum degassing to obtain slurry A, which is the first negative electrode active material layer; Step ②: Preparation of the second negative electrode active material layer; The second conductive agent powder and the second binder powder are mixed and stirred, and then moistened with solvent; The mixture is diluted with solvent, stirred, dispersed, kneaded and scraped, and then premixed second carbon-based active material and second silicon-based active material are added to form a mixture to make the mixture wet; After dilution with solvent, stirring, dispersing, kneading and scraping are performed, followed by vacuum degassing to obtain slurry B, which is the second negative electrode active material layer; Step ③: Preparation of lithium battery negative electrode sheet; The first negative electrode active material layer is coated on the current collector, and the second negative electrode active material layer is coated on the first negative electrode active material layer. After drying, an electrode material layer is formed on the current collector, and then the electrode is rolled to obtain a lithium battery negative electrode sheet. Step 4: Assemble the lithium battery negative electrode, positive electrode, electrolyte, and separator to obtain the lithium battery.
[0020] Compared with the prior art, the present invention has the following beneficial effects: This invention utilizes the particle size matching of silicon-based and carbon-based materials, and employs theoretical calculation formulas. A reasonable particle size combination of silicon-carbon and graphite, i.e., a formulation with different porosities in the upper and lower layers, is obtained. Under the same pressure, active layers with different porosities are formed. That is, a negative electrode sheet with a double porosity structure can be prepared in one rolling process. By setting a double-layer structure on the negative electrode through double coating, the first negative electrode active material layer near the current collector is a high-compact, low-porosity layer, and the second negative electrode active material layer near the separator is a low-compact, high-porosity layer. At the same time, rod-shaped mesoporous materials are added to the high-compact, low-porosity layer to further improve liquid absorption and build a fast lithium-ion diffusion channel in the negative electrode. This ensures high energy density while significantly improving fast charging performance. Moreover, the method is simple and can be mass-produced.
[0021] In addition to the objectives, features, and advantages described above, the present invention has other objectives, features, and advantages. The invention will now be described in further detail with reference to the figures. Attached Figure Description
[0022] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 This is a schematic diagram of the structure of a lithium battery negative electrode sheet in an embodiment of the present invention; Figure 2 This is a schematic diagram of the coating process of a lithium battery negative electrode sheet in an embodiment of the present invention; Figure 3 This is a schematic diagram of the structure of the first active material and the rod-shaped mesoporous liquid-absorbing material of a lithium battery negative electrode sheet in an embodiment of the present invention.
[0023] in: 1. Current collector; 2. First negative electrode active material layer; 201. First active material; 202. Rod-shaped mesoporous liquid-absorbing material; 3. Second negative electrode active material layer. Detailed Implementation
[0024] To make the above-mentioned objectives, features, and advantages of the present invention clearer and easier to understand, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be noted that the accompanying drawings of the present invention are all in a simplified form and use non-precise proportions, and are only used to facilitate and clearly assist in illustrating the implementation of the present invention; the "several" mentioned in the present invention are not limited to the specific number shown in the examples in the accompanying drawings; the orientations or positional relationships indicated by terms such as "front," "middle," "rear," "left," "right," "up," "down," "top," "bottom," and "middle" mentioned in the present invention are all based on the orientations or positional relationships shown in the accompanying drawings of the present invention, and do not indicate or imply that the device or component referred to must have a specific orientation, nor should they be construed as limitations on the present invention.
[0025] Example 1: See Figures 1 to 3 As shown, the lithium battery negative electrode sheet provided by the present invention includes a current collector 1, a first negative electrode active material layer 2, and a second negative electrode active material layer 3. The current collector 1 is configured as a copper foil; specifically, in this embodiment, the current collector 1 is preferably any one or any combination of two or more of composite copper foil, carbon-coated copper foil, perforated carbon-coated copper foil and perforated composite copper foil. The first negative electrode active material layer is disposed between the current collector and the second negative electrode active material layer; The second negative electrode active material layer is disposed on the surface of the first negative electrode active material layer.
[0026] Preferably, in this embodiment, the volume fraction of the particle size in the first negative electrode active material layer 2 and the second negative electrode active material layer 3 is set to be... The particle size of any particle size in the particle size distribution curve of the active substance is . The minimum particle size in the particle size distribution curve of the active substance is The maximum particle size in the particle size distribution curve of the active substance is and the particle size distribution modulus of the active material particles is Specifically, in this embodiment, the particle size distribution in both the first negative electrode active material layer 2 and the second negative electrode active material layer 3 is set to... Among them, the particle size distribution modulus of the active material particles in the first negative electrode active material layer The range of values is set to The preferred value is 0.37 as the particle size distribution modulus of the active material. The ideal value for the densest packing; particle size distribution modulus of active material particles in the second negative electrode active material layer. The range of values is set to >0.6 or <0.2. This is to ensure that the first negative electrode active material layer has a higher compaction density and the second negative electrode active material layer has a lower compaction density.
[0027] Preferably, in this embodiment, the limiting compaction density of the first negative electrode active material layer 2 is set to be The ultimate compaction density of the second negative electrode active material layer 3 is: ,satisfy and Specifically, in this embodiment, Values , Values .
[0028] As a further embodiment, the first negative electrode active material layer 2 includes a first active material 201, a first conductive agent, a first dispersant, a first binder, and a rod-shaped mesoporous liquid-absorbing material 202; The first active material 201 includes a first carbon-based active substance and a first silicon-based active substance; The rod-shaped mesoporous liquid-absorbing material 202 is configured as a rod-shaped mesoporous tin-based material with a pore size of 2nm to 100nm. It has open channels and a large pore volume, which improves rate performance while ensuring high compaction and low porosity.
[0029] Preferably, in this embodiment, the first silicon-based active material is a silicon-based anode material.
[0030] Preferably, in this embodiment, the mass percentages of the first active material 201, the first conductive agent, the first dispersant, the first binder, and the rod-shaped mesoporous liquid-absorbing material 202 are set as follows: 90-99 wt% of the first active material 201, 0.01-3 wt% of the first conductive agent, 0-3 wt% of the first dispersant, 0.01-5 wt% of the first binder, and 0.01-1 wt% of the rod-shaped mesoporous liquid-absorbing material 202.
[0031] As a further embodiment, the second negative electrode active material layer 3 includes a second active material, a second conductive agent, a second dispersant, and a second binder; the second active material includes a second carbon-based active material and a second silicon-based active material; the mass percentage content of the second active material, the second conductive agent, the second dispersant, and the second binder is set to 90-99 wt% of the second negative electrode active material, 0.01-3 wt% of the second conductive agent, 0-3 wt% of the second dispersant, and 0.01-5 wt% of the second binder.
[0032] Preferably, in this embodiment, the volume average particle size of the first carbon-based active material is set to be The volume average particle size of the second carbon-based active material is The volume average particle size of the first silicon-based active material is And the volume average particle size of the second silicon-based active material is Specifically, in this embodiment, , , The value ranges from 8μm to 23μm. The value ranges from 4μm to 16μm. The value ranges from 6μm to 12μm. The particle size ranges from 2μm to 5μm. In this invention, the lower carbon-based active material is set to a higher particle size to improve its energy density, and the upper carbon-based active material is set to a smaller particle size to improve rate performance.
[0033] Preferably, in this embodiment, the first conductive agent is any one or any combination of two or more of the following: conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotube, graphene, metal powder and metal fiber. The second conductive agent is set as any one or any combination of two or more of the following: conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotube, graphene, metal powder and metal fiber.
[0034] In a further preferred embodiment, the first conductive agent and the second conductive agent may be configured to have the same structure or different structures.
[0035] Preferably, in this embodiment, the first adhesive is set as any one or any combination of two or more of the following: styrene-butadiene rubber, polyacrylic acid, lithium polyacrylate, carboxymethyl chitosan, sodium alginate, polyvinyl alcohol, polyurethane, polyvinylidene fluoride, and polyvinylidene fluoride-hexafluoropropylene copolymer. The second adhesive is set as any one or any combination of two or more of the following: styrene-butadiene rubber, polyacrylic acid, lithium polyacrylate, carboxymethyl chitosan, sodium alginate, polyvinyl alcohol, polyurethane, polyvinylidene fluoride, and polyvinylidene fluoride-hexafluoropropylene copolymer.
[0036] In a further preferred embodiment, the first adhesive and the second adhesive may be configured to have the same structure or different structures.
[0037] Preferably, in this embodiment, the first dispersant is lithium carboxymethyl cellulose and / or sodium carboxymethyl cellulose; The second dispersant is configured as lithium carboxymethyl cellulose and / or sodium carboxymethyl cellulose.
[0038] More preferably, the first dispersant and the second dispersant may be configured to have the same structure or different structures.
[0039] Preferably, the first carbon-based active material is any one or any combination of two or more of natural graphite, artificial graphite or hard carbon. The second carbon-based active material is set as any one or any combination of two or more of natural graphite, artificial graphite or hard carbon.
[0040] More preferably, the first carbon-based active material and the second carbon-based active material can be configured with the same structure or different structures.
[0041] As a further embodiment, the first silicon-based active material has a mass percentage of 3-50 wt% in the first negative electrode active material layer 2, and the second silicon-based active material has a mass percentage of 1-40 wt% in the second negative electrode active material layer 3. The mass percentage of the first silicon-based active material in the first negative electrode active material layer 2 is greater than or equal to the mass percentage of the second silicon-based active material in the second negative electrode active material layer 3.
[0042] As a further embodiment, the mass ratio of the first negative electrode active material layer 2 to the second negative electrode active material layer 3 is 1:9 to 9:1, for example, 1:9, 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, or 9:1. The lower the proportion of the first negative electrode active material layer 2 and the higher the proportion of the second negative electrode active material layer 3, the stronger the lithium intercalation capability of the negative electrode, that is, the improved rate performance.
[0043] Preferably, the chemical substances involved in this invention and their CAS numbers are shown in Table 1.
[0044] Table 1. Statistical table of chemical substances involved in this invention and their CAS numbers.
[0045] Example 2: The present invention also provides a lithium battery, including a positive electrode, an electrolyte, a separator, and a lithium battery negative electrode as described in Example 1.
[0046] Example 3: This invention also provides a method for preparing a lithium battery, comprising the following steps: S1. The first conductive agent powder, the first binder powder and the rod-shaped mesoporous liquid-absorbing material 202 are mixed and stirred, and a solvent is added to wet them. The solvent is preferably deionized water. Then, the mixture is diluted with solvent, stirred, dispersed, kneaded and scraped. Then, the pre-mixed first carbon-based active material and the first silicon-based active material are added to form a mixture to wet the mixture. Then, the mixture is diluted with solvent, stirred, dispersed, kneaded and scraped. Then, vacuum degassing is performed to obtain slurry A, which is the first negative electrode active material layer 2. S2. Mix and stir the second conductive agent powder and the second binder powder, add solvent to moisten, then dilute with solvent, stir, disperse, knead and scrape the material, then add the pre-mixed second carbon-based active material and the second silicon-based active material to form a mixture, so as to moisten the mixture, then dilute with solvent, stir, disperse, knead and scrape the material, and then perform vacuum degassing to obtain slurry B, which is the second negative electrode active material layer 3; S3. Use a double-layer coating machine, such as Figure 2 The coating machine has three dies and can output materials in two layers. It coats the first negative electrode active material layer 2 onto the current collector 1 and the second negative electrode active material layer 3 onto the first negative electrode active material layer 2. After drying, an electrode material layer is formed on the current collector 1, and then the electrode is obtained by rolling.
[0047] S4. Assemble the negative electrode obtained in S3 with the positive electrode, electrolyte and separator to prepare a lithium-ion battery, and obtain the battery. The positive electrode active material in the positive electrode is any one or any combination of two or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium-rich manganese and lithium iron phosphate.
[0048] In the following examples, the particle size test method is GB / T19077-2024 "Particle Size Analysis by Laser Diffraction". The test method for the limit compaction density of the electrode is as follows: negative electrode sheets with different compaction densities are prepared by silicon-based, carbon-based, conductive agent, dispersant and binder. After these electrode sheets are rolled, SEM is taken to observe the particle integrity and determine the maximum compaction density of the material system.
[0049] Negative electrode active layer formulation determination: Silicon-based active particle size was obtained by laser particle size analyzer testing. and carbon-based active substances The particle size of the active material is calculated based on the ratio of silicon-based to carbon-based components in the active material layer. ,calculate Obtain the coefficient Among them, the particle size distribution modulus is 0.27 < <0.47, exhibiting high compaction density; among which >0.6 or <0.2, with a low compaction density; the high compaction density active material is used as the first negative electrode active material layer 2, and the low compaction density active material is used as the second negative electrode active material layer 3.
[0050] Experimental Example 1: (a) Preparation of negative electrode sheet: S1. The first conductive agent powder, the first binder powder, and the rod-shaped mesoporous liquid-absorbing material 202 are mixed and stirred; a solvent is added to wet the mixture, preferably deionized water, and then the mixture is diluted, stirred, dispersed, kneaded, and scraped with the solvent; then a pre-mixed mixture of the first carbon-based active material and the first silicon-based active material is added to wet the mixture, and then the mixture is diluted, stirred, dispersed, kneaded, and scraped with the solvent, and then vacuum degassing is performed to obtain slurry A, which is the first negative electrode active material layer 2.
[0051] S2. Mix and stir the second conductive agent powder and the second binder powder; add solvent to moisten, then dilute with solvent, stir, disperse, knead and scrape the material; then add the pre-mixed mixture of the second carbon-based active material and the second silicon-based active material to moisten the mixture, then dilute with solvent, stir, disperse, knead and scrape the material, and then perform vacuum degassing to obtain slurry B, which is the second negative electrode active material layer 3.
[0052] S3. Use a double-layer coating machine, such as Figure 2 The coating machine has three dies and can output materials in two layers. It coats the first negative electrode active material layer 2 onto the current collector 1 and the second negative electrode active material layer 3 onto the first negative electrode active material layer 2. After drying, an electrode material layer is formed on the current collector 1, and then the negative electrode is obtained by rolling.
[0053] (II) Preparation of the positive electrode sheet: The positive electrode active material lithium nickel cobalt manganese oxide, conductive carbon black, and binder are mixed in a mass ratio of 97:1.5:1.5. Then, N-methylpyrrolidone is added and stirred to disperse the mixture to prepare a positive electrode slurry. The positive electrode slurry is coated onto the positive electrode current collector 1 using a double-layer coating method. The mixture is then dried, rolled, slit, and sheeted to obtain the positive electrode sheet.
[0054] (III) Battery fabrication: The above-mentioned positive electrode, negative electrode, electrolyte and separator were assembled to prepare a lithium-ion battery, resulting in a 3.5Ah soft-pack battery. The rate performance and cycle performance were then tested.
[0055] The mass ratio of each substance in the battery slurry prepared in Experiment Example 1 is shown in Table 2. The mass ratio of each component is: silicon-based: carbon-based: conductive agent: dispersant: binder: rod-shaped mesoporous liquid absorbent material 202.
[0056] Experimental Example 2: Experimental Example 2 was prepared in the same manner as Experimental Example 1, except that the selection of silicon-based and carbon-based active materials was different, the mass ratio of each component in the negative electrode slurry was different, and the coating was single-layer or double-layer. See Table 2 for the mass ratio of each substance in the slurry. The mass ratio of each component is: silicon-based: carbon-based: conductive agent: dispersant: binder: rod-shaped mesoporous liquid absorbent material 202.
[0057] Experimental Example 3: Experimental Example 3 was prepared in the same manner as Experimental Example 1, except that the selection of silicon-based and carbon-based active materials was different, the mass ratio of each component in the negative electrode slurry was different, and the coating was single-layer or double-layer. See Table 2 for the mass ratio of each component in the slurry. The mass ratio of each component is: silicon-based: carbon-based: conductive agent: dispersant: binder: rod-shaped mesoporous liquid absorbent material 202. In Experimental Example 3, the negative electrode current collector 1 was coated with a layer of slurry on both sides, which is a single-layer coating.
[0058] Comparative Example 1: Comparative Example 1 was prepared in the same manner as Experimental Example 1, except that two layers of slurry were coated on both sides of the negative electrode current collector 1, and the sum of the thicknesses of the two negative electrode active material layers formed by the two slurry layers was 170 μm. See Table 2 for the mass ratio of each substance in the slurry.
[0059] Comparative Example 2: Comparative Example 2 was prepared using the same method as in Experimental Example 1, except that in Comparative Example 2, a layer of slurry was coated on both the front and back sides of the negative electrode current collector 1, and the thickness of the negative electrode active material layer formed by the slurry was 170 μm. See Table 2 for the mass ratio of each substance in the slurry.
[0060] Comparative Example 3: Comparative Example 2 was prepared using the same method as in Experimental Example 1, except that in Comparative Example 2, a layer of slurry was coated on both the front and back sides of the negative electrode current collector 1, and the thickness of the negative electrode active material layer formed by the slurry was 170 μm. See Table 2 for the mass ratio of each substance in the slurry.
[0061] Comparative Example 4: Comparative Example 1 was prepared in the same manner as Experimental Example 1, except that two layers of slurry were coated on both sides of the negative electrode current collector 1, and the sum of the thicknesses of the two negative electrode active material layers formed by the two slurry layers was 170 μm. See Table 2 for the mass ratio of each substance in the slurry.
[0062] Comparative Example 5: Comparative Example 1 was prepared in the same manner as Experimental Example 1, except that two layers of slurry were coated on both sides of the negative electrode current collector 1, and the sum of the thicknesses of the two negative electrode active material layers formed by the two slurry layers was 170 μm. See Table 2 for the mass ratio of each substance in the slurry.
[0063] The experimental parameters for Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 are shown in Table 2.
[0064] Table 2. Statistical table of experimental parameters for Examples 1-3 and Comparative Examples 1-5
[0065] Compaction and porosity tests were performed on Experimental Example 1, Comparative Example 2 and Comparative Example 3. The parameters are shown in Table 3. Based on Tables 2, 3, and 4, the results are as follows: Based on the lithium-ion battery performance test results of Experimental Examples 1-3 and Comparative Examples 1-5, the rate performance was compared as follows: At 25℃, charge and discharge tests were conducted at 0.5C / 0.5C, 1C / 1C, 2C / 2C and 3C / 3C, with a voltage range of 2.5-4.25V, and the 0.5C / 0.5C discharge capacity was used as the baseline capacity. Cycling performance comparison: At 25℃, 1C / 1C cycling, voltage range of 2.5-4.25V, capacity retention rate at the 500th cycle.
[0066] As can be seen from the data in Table 2, the particle size distribution of the active material meets the requirements. , where 0.27 < <0.47, it has a higher ultimate compaction and lower porosity. >0.6 or <0.2 indicates a lower ultimate compaction and higher porosity.
[0067] Table 3. Compaction and porosity test parameters for Experiment 1, Comparative Example 2, and Comparative Example 3.
[0068] Battery performance tests were conducted on Experimental Examples 1-3 and Comparative Examples 1-5, as detailed in Table 4: Table 4 Battery performance test data for Experimental Examples 1-3 and Comparative Examples 1-5
[0069] As can be seen from the data in Table 3, under the same roller pressure, Comparative Example 2 has higher compaction and lower porosity than Comparative Example 3. Under the same rolling pressure, the compaction and porosity of Example 1 are between those of Comparative Example 2 and Comparative Example 3. The particle size distribution of the first negative electrode active material layer 2 and the second negative electrode active material layer 3 in Example 1 are quite different. Under the same rolling pressure, the first negative electrode active material layer 2 tends to be compacted with low porosity, while the second negative electrode active material layer 3 tends to be compacted with high porosity.
[0070] As can be seen from the data in Table 4, compared with Comparative Example 2 and Comparative Example 3, Experimental Example 1 has a higher 2C and 3C capacity retention rate, and also a better 500-cycle 1C / 1C capacity retention rate. This is because Example 1 has a double-layer porosity structure, and the first negative electrode active material layer 2 is more compact and has lower porosity, which is beneficial to improving energy density. The second negative electrode active material layer 3 has a loose structure and higher porosity, which is conducive to electrolyte wetting and improves rate performance. The outermost second negative electrode active material layer 3 with large pores enhances the wetting of electrolyte in the electrode. The contact surface between the negative electrode active material and the electrolyte is larger, which reduces polarization and improves the utilization rate of the negative electrode active material, thereby reducing interfacial impedance and charge transfer impedance.
[0071] Compared to Experimental Example 1, the battery in Comparative Example 1 has poorer 2C and 3C capacity retention and also poorer cycle performance. The low porosity of the outer layer structure is not conducive to electrolyte wetting, which increases polarization, improves interfacial impedance and charge transfer impedance, and is detrimental to rate performance and cycle stability.
[0072] Compared to Experiment 1, Experiment 2, with comparable capacity retention rates at 2C and 3C, exhibits higher capacity retention and less thickness expansion at 500 cycles at 1C / 1C. This is because the first negative electrode active material layer 2 has a high silicon content, while also increasing the active material layer bonding content, which tightly bonds the active material to the current collector 1, improving expansion and increasing cycle life.
[0073] Compared to Comparative Examples 4 and 5, Experimental Example 2 exhibits higher 2C and 3C capacity retention rates (slightly lower than Comparative Example 5), and also better 500-cycle 1C / 1C capacity retention rate (significantly better than Comparative Examples 4 and 5). This is because Experimental Example 2 has a bilayer porosity structure. The first negative electrode active material layer 2 is more compact and has lower porosity, which is beneficial for improving energy density, while the second negative electrode active material layer 3 has a looser structure and higher porosity, which is beneficial for electrolyte wetting and improving rate performance. The large pore structure of the outer layer enhances electrolyte wetting in the electrode, reduces polarization, and improves the utilization rate of active material, thereby reducing interfacial impedance and charge transfer impedance.
[0074] Compared to Comparative Example 2, Experimental Example 3 showed a slight improvement in capacity retention at 2C and 3C, while exhibiting higher capacity retention and less thickness expansion at 500 cycles of 1C / 1C. This is because the first negative electrode active material layer 2 contains mesoporous tin oxide, which can significantly improve the liquid absorption of the high-density electrode, increase the diffusion channels of lithium ions in the high-density low-porosity layer, improve the diffusion rate, and further improve the rate performance of the negative electrode.
[0075] Based on the above, the following conclusions can be drawn: (1) Compared with Comparative Example 2, the first negative electrode active material layer 2 of this scheme contains rod-shaped mesoporous liquid-absorbing material 202, which can significantly improve the liquid absorption of the high-density electrode sheet, construct a fast lithium-ion diffusion channel, shorten the diffusion path of lithium ions in the high-density, low-porosity layer, improve the diffusion rate, and further improve the rate performance of the negative electrode. (2) Compared with the double-layer coating structure with the same proportion of silicon content in the upper and lower layers, such as Comparative Example 1, or the double-layer coating structure with a high silicon content in the upper layer, such as Comparative Example 4, the negative electrode sheet prepared by this scheme in Experimental Example 2 can further improve the negative electrode rate performance without losing cycle life. (3) Compared with the double-layer coating structure with different particle sizes on the upper and lower layers, such as Comparative Example 1, the outer layer of this scheme has high porosity, which is conducive to electrolyte wetting, reduces polarization, improves interface impedance and charge transfer impedance, and is conducive to improving rate performance and cycle stability.
[0076] (4) Compared with conventional structures with the same silicon content, such as Comparative Example 2 and Comparative Example 3, the negative electrode sheet prepared by this scheme in Experiment Example 1 can improve the rate performance of the battery without compromising the cycle performance. This solution uses the particle size distribution formula. It can quickly screen out the first negative electrode active material layer 2 and the second negative electrode active material layer 3 that conform to the porosity gradient, which is convenient for industrial mass production applications.
[0077] This invention utilizes the particle size matching of silicon-based and carbon-based materials, and employs theoretical calculation formulas. A reasonable particle size combination of silicon-carbon and graphite, i.e., a formula with different porosities in the upper and lower layers, is obtained. Under the same pressure, active layers with different porosities are formed. That is, a negative electrode sheet with a double porosity structure can be prepared in one rolling process. A double-layer structure is set in the negative electrode sheet by double coating. The first negative electrode active material layer 2 near the current collector 1 is a high-compact, low-porosity layer, and the second negative electrode active material layer 3 near the separator is a low-compact, high-porosity layer. At the same time, rod-shaped mesoporous materials are added to the high-compact, low-porosity layer to further improve liquid absorption and build a fast lithium-ion diffusion channel in the negative electrode. This ensures high energy density while significantly improving fast charging performance. Moreover, the method is simple and can be mass-produced.
[0078] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A lithium battery negative electrode sheet, characterized in that, It includes a current collector, a first negative electrode active material layer, and a second negative electrode active material layer; The current collector is made of copper foil; The first negative electrode active material layer is disposed between the current collector and the second negative electrode active material layer; The second negative electrode active material layer is disposed on the surface of the first negative electrode active material layer; Let the volume fraction of the particle size of the material in the first and second negative electrode active material layers be . The particle size of any particle size in the particle size distribution curve of the active substance is . The minimum particle size in the particle size distribution curve of the active substance is The maximum particle size in the particle size distribution curve of the active substance is and the particle size distribution modulus of the active material particles is ; The particle size distribution in both the first and second negative electrode active material layers is set to... ; Volume fraction of particle size The value range is set to 0 to 100%; The particle size distribution modulus of the active material particles in the first negative electrode active material layer The range of values is set to ; The particle size distribution modulus of the active material particles in the second negative electrode active material layer The range of values is set to >0.6 or <0.
2.
2. The lithium battery negative electrode sheet according to claim 1, characterized in that, Let the limiting compaction density of the first negative electrode active material layer be... The ultimate compaction density of the second negative electrode active material layer is ,satisfy and .
3. The lithium battery negative electrode sheet according to claim 1 or 2, characterized in that, The first negative electrode active material layer includes a first active material, a first conductive agent, a first dispersant, a first binder, and a rod-shaped mesoporous liquid-absorbing material; The first active material includes a first carbon-based active substance and a first silicon-based active substance; The rod-shaped mesoporous liquid-absorbing material is configured as a rod-shaped mesoporous tin-based material, and its pore size is configured as 2nm to 100nm.
4. The lithium battery negative electrode sheet according to claim 3, characterized in that, The mass percentages of the first active material, the first conductive agent, the first dispersant, the first binder, and the rod-shaped mesoporous liquid-absorbing material are set as follows: 90-99 wt% of the first active material, 0.01-3 wt% of the first conductive agent, 0-3 wt% of the first dispersant, 0.01-5 wt% of the first binder, and 0.01-1 wt% of the rod-shaped mesoporous liquid-absorbing material.
5. The lithium battery negative electrode sheet according to claim 4, characterized in that, The second negative electrode active material layer includes a second active material, a second conductive agent, a second dispersant, and a second binder; The second active material includes a second carbon-based active substance and a second silicon-based active substance; The mass percentages of the second active material, the second conductive agent, the second dispersant, and the second binder are set as follows: 90-99 wt% of the second negative electrode active material, 0.01-3 wt% of the second conductive agent, 0-3 wt% of the second dispersant, and 0.01-5 wt% of the second binder.
6. The lithium battery negative electrode sheet according to claim 5, characterized in that, Let the volume average particle size of the first carbon-based active material be... The volume average particle size of the second carbon-based active material is The volume average particle size of the first silicon-based active material is And the volume average particle size of the second silicon-based active material is ; in: , , The value ranges from 8μm to 23μm. The value ranges from 4μm to 16μm. The value ranges from 6μm to 12μm. The value ranges from 2μm to 5μm.
7. The lithium battery negative electrode sheet according to claim 5, characterized in that, The first conductive agent is set as any one or any combination of two or more of the following: conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotube, graphene, metal powder and metal fiber. The second conductive agent is set as any one or any combination of two or more of the following: conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotube, graphene, metal powder and metal fiber.
8. The lithium battery negative electrode sheet according to claim 5, characterized in that, The first adhesive is set as any one or any combination of two or more of the following: styrene-butadiene rubber, polyacrylic acid, lithium polyacrylate, carboxymethyl chitosan, sodium alginate, polyvinyl alcohol, polyurethane, polyvinylidene fluoride, and polyvinylidene fluoride-hexafluoropropylene copolymer. The second adhesive is set as any one or any combination of two or more of the following: styrene-butadiene rubber, polyacrylic acid, lithium polyacrylate, carboxymethyl chitosan, sodium alginate, polyvinyl alcohol, polyurethane, polyvinylidene fluoride, and polyvinylidene fluoride-hexafluoropropylene copolymer.
9. The lithium battery negative electrode sheet according to claim 5, characterized in that, The first dispersant is lithium carboxymethyl cellulose and / or sodium carboxymethyl cellulose; The second dispersant is configured as lithium carboxymethyl cellulose and / or sodium carboxymethyl cellulose.
10. The lithium battery negative electrode sheet according to claim 5, characterized in that, The first carbon-based active material is set as any one or any combination of two or more of natural graphite, artificial graphite or hard carbon. The second carbon-based active material is set as any one or any combination of two or more of natural graphite, artificial graphite or hard carbon.
11. The lithium battery negative electrode sheet according to claim 10, characterized in that, The first silicon-based active material has a mass percentage of 3-50 wt% in the first negative electrode active material layer, and the second silicon-based active material has a mass percentage of 1-40 wt% in the second negative electrode active material layer. The mass percentage of the first silicon-based active material in the first negative electrode active material layer is greater than or equal to the mass percentage of the second silicon-based active material in the second negative electrode active material layer. The mass ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:9 to 9:
1.
12. A lithium battery, characterized in that, It includes a positive electrode, an electrolyte, a separator, and a lithium battery negative electrode as described in claim 11.
13. A method for preparing a lithium battery as described in claim 12, characterized in that, Includes the following steps: Step ①: Preparation of the first negative electrode active material layer; The first conductive agent powder, the first binder powder, and the rod-shaped mesoporous liquid-absorbing material are mixed and stirred, and then moistened with solvent; The mixture is diluted with solvent, stirred, dispersed, kneaded and scraped, and then premixed first carbon-based active material and first silicon-based active material are added to form a mixture to make the mixture wet; After dilution with solvent, stirring, dispersing, kneading and scraping are performed, followed by vacuum degassing to obtain slurry A, which is the first negative electrode active material layer; Step ②: Preparation of the second negative electrode active material layer; The second conductive agent powder and the second binder powder are mixed and stirred, and then moistened with solvent; The mixture is diluted with solvent, stirred, dispersed, kneaded and scraped, and then premixed second carbon-based active material and second silicon-based active material are added to form a mixture to make the mixture wet; After dilution with solvent, stirring, dispersing, kneading and scraping are performed, followed by vacuum degassing to obtain slurry B, which is the second negative electrode active material layer; Step ③: Preparation of lithium battery negative electrode sheet; The first negative electrode active material layer is coated on the current collector, and the second negative electrode active material layer is coated on the first negative electrode active material layer. After drying, an electrode material layer is formed on the current collector, and then the electrode is rolled to obtain a lithium battery negative electrode sheet. Step 4: Assemble the lithium battery negative electrode, positive electrode, electrolyte, and separator to obtain the lithium battery.
